Faktor-Faktor Yang Mempengaruhi Peningkatan Kadar Gula Darah Pada Pasien Diabetes Mellitus Tipe-2 - Saharuddin; Dwi Ghita; I Kadek Dwi Swarjana; Avita Nona Yani; Nur, Akbar (Journal Kiara : Nursing and Midwifery, 2024)
Diabetes Mellitus is a chronic disease that the sufferer will suffer throughout their life. Diabetes mellitus is usually known as the mother of disease. Type-2 DM is caused by several factors including obesity, physical activity/exercise, age, wrong lifestyle and unhealthy eating habits. Objective: This study aims to analyze/explain the factors that influence the increase in blood sugar levels in type 2 DM patients. Method: The method used in writing this literature review is internet search from databases with high and medium quality criteria, namely Scopus, ProQuest, Pubmed, CINAHL and Scient Direct, but several journals also use several health links such as Curren Nursing and others, using keywords (factors, increased blood sugar levels & type 2 DM). Results & Analysis: Of the 15 articles from 2016 to 2020 that met the inclusion criteria that were obtained and analyzed, there were 12 articles/journals using a Cross Sectional Study design, Literature Review (1 article/research), Quantitative descriptive (1 article/research) , and Accidental sampling (1 article/research), then there are 7 articles/journals discussing physical activity, 6 articles/journals discussing eating patterns/diet, 5 articles/journals discussing anxiety/stress levels, 3 articles/journals each discussing about (knowledge & family support) and 2 articles/journals each discussing (genetics & certain diseases) on increasing blood sugar levels in type 2 DM patients. Conclusion & Suggestions: there are various factors that can increase blood sugar levels, both factors that cannot be changed (genetics & certain diseases) or factors that can be changed (physical activity, eating patterns/diet, anxiety/stress levels, knowledge & family support). So it is recommended that type 2 DM sufferers adopt a healthy lifestyle so that their blood sugar can be controlled or decreased.